Implementation of Mathventure in Strengthening Students’ Numeracy Skills at Hegarmanah Islamic Junior High School - Komala, Elsa; Nurjannati, Ditia Tazkiyatunnisa; Manora, Elsa; Maulidsyi, Muhammad Irsya (Jurnal Pengabdian Sains dan Humaniora, 2025)
Numeracy skills are a crucial aspect in supporting students' skills in facing real-life challenges. This article explains the implementation of Mathventure in Community Service activities integrated into the Campus Mengajar Batch 8 activities in 2024 at Hegarmanah Islamic Junior High School, Sukabumi Regency, as an innovation in project-based contextual numeracy learning. This program aims to improve numeracy understanding and interest in mathematical concepts through an approach that is relevant to everyday life. The subjects consisted of 30 students from class VIII who would carry out the Minimum Competency Assessment. The methods used included the Minimum Competency Assessment test, observation, interviews, and documentation. The program was implemented in three stages: pre-assignment, implementation of activities and the final stage of assignments. The results of the activities showed an increase in participation, understanding of concepts, and 21st century skills such as critical thinking, collaboration, and communication. The pre-test score results ranged from 5–45, while the post-test showed an increase with a range of 30–80. These findings show that the Mathventure program with a project-based approach has proven effective in bridging the gap between theory and practice, as well as strengthening the character of active and independent learning of students.